Integrating Socio-Cultural Realities into Differentiated Instruction: A Modular Approach - Yahrif, Muhamad; Yassi, Abdul Hakim; Pammu, Abidin (Proceedings of International Conference on Science, Education, and Technology, 2025)
This research aims to develop differentiated instruction through a socio-cultural module for Junior high school teachers. This research used a Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The analysis was carried out by analysing teachers’ and students’ problems, implementing differentiated instruction, and teachers' and students’ needs. Then, the module will be designed and developed by validating and revising the product through three education experts as validators. Next, implementation and evaluation were conducted in 2 junior high schools with a sample of 185 students, 1 school supervisor, 2 headmasters, and 10 teachers. After being validated by three education experts, this module was revised, then implemented in 2 junior high schools in Soppeng, Indonesia. The result of this study showed positive feedback from validators which reached 98.4 % satisfaction. However, some feedback were given to improve this module. After some revisions, the module was implemented in two junior high schools in Soppeng and reached an average score of 99.5 % from four aspects: utility, feasibility, accuracy, and propriety of the module. In terms of students' satisfaction related to teachers’ method of delivering material using a social culture approach to differentiated instruction, 77.7% was achieved, which showed students feel very satisfied with differentiated instruction with a socio-cultural approach. Based on this result, the teaching module for differentiated instruction with a social-culture approach is valid and practical, so it qualifies as a feasible and quality development product.